The population densities of potentially toxic epiphytic dinoflagellates in Lingsat Reef, La Union Province, Philippines - Pocsidio, Glorina N.; Dimaano, Luzviminda M. (2004)
The population densities of ciguatera-associated dinoflagellates in Lingsat Reef, La Union Province, Philippines were monitored in April, June, and August 1999 and monthly in the year 2000, except in January, July, and November. The survey was conducted to find a valid basis for the occurrence in 1996 of a suspect ciguatera incident in the vicinity. Gambierdiscus, Ostreopsis and Prorocentrum species, known progenitors of ciguateric toxins, were surveyed on the macroalgae and seagrass found in a stretch of reef that extended about 1 km along the shoreline, at a distance up to 0.5 km from the shoreline, and a depth of 1 m. Gambierdiscus sp. was not observed in 1999 but in 2000 it had the highest density of only 6.0 cells per g brown alga Dictyota linearis. Similarly, Prorocentrum spp. Peaked in 1999 at 91.9 cells oer f red alga Gelidiella acerosa but maximum density in 2000 was 43.1 cells per g Dictyota linearis. The data suggest a potential for ciguateric episodes in the Lingsat Reef with the most likely involvement of Ostreopsis spp., Ostreopsis lenticularis, in particular, although the presence especially of Prorocentrum spp. could implicate this genus in a ciguateric event.
Keywords: Food poisoning; Genetic polymorphisms; Reef fishes